Binge ethanol exposure during adolescence leads to a persistent loss of neurogenesis in the dorsal and ventral hippocampus that is associated with impaired adult cognitive functioning - Vetreno, Ryan P.; Crews, Fulton T. (Frontiers in Neuroscience, 2015)
Adolescence is a developmental period that coincides with the maturation of adult cognitive faculties. Binge drinking is common during adolescence and can impact brain maturation. Using a rodent model of adolescent intermittent ethanol (AIE; 5.0 g/kg, i.g., 20% EtOH w/v; 2 days on/2 days off from postnatal day [P]25 to P55), we discovered that AIE treatment reduced neurogenesis (i.e., doublecortin-immunoreactive [DCX+IR] cells) in both the dorsal and ventral hippocampal dentate gyrus of late adolescent (P56) male Wistar rats that persisted during abstinence into adulthood (P220). This reduction in neurogenesis was accompanied by a concomitant reduction in proliferating cells (Ki-67) and an increase in cell death (cleaved caspase-3). In the hippocampus, AIE treatment induced a long-term upregulation of neuroimmune genes, including Toll-like receptor 4 (TLR4) and its endogenous agonist high-mobility group box 1 as well as several proinflammatory signaling molecules. Administration of lipopolysaccharide, a gram-negative endotoxin agonist at TLR4, to young adult rats (P70) produced a similar reduction of DCX+IR cells that was observed in AIE-treated animals. Behaviorally, AIE treatment impaired object recognition on the novel object recognition task when assessed from P163 to P165. Interestingly, object recognition memory was positively correlated with DCX+IR in both the dorsal and ventral hippocampal dentate gyrus while latency to enter the center of the apparatus was negatively correlated with DCX+IR in the ventral dentate gyrus. Together, these data reveal that adolescent binge ethanol exposure persistently inhibits neurogenesis throughout the hippocampus, possibly through neuroimmune mechanisms, which might contribute to altered adult cognitive and emotive function.